RELATIONSHIPS BETWEEN SPIRITUALITY, MINDFULNESS, AND SOCIAL SUPPORT WITH PSYCHOLOGICAL WELLBEING OF ELDERLY - Verma, Anjali; Rawat, Ved Prakash; Gupta, Garima (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose of the study was to examine the relationship between spirituality, mindfulness and social support (total and dimensions) with psychological wellbeing (total and dimensions). The sample of the present study was conducted on Total 200 elderly people with purposive sampling technique, within the age range from 60 to 75 years (Age Mean = 68.80, S.D. = 3.69). Sample was taken from various places of Varanasi and Chandauli district of Uttar Pradesh. Researcher was used self-report questionnaires for taking response of participants for studied variables. In this study total four tools namely - The Spiritual Personality Inventory-Revised, Five Facet Mindfulness Questionnaire-H (FFMQ-H), Social Support Scale and Psychological Well Being Scale (PWBS) were used. For knowing the relationship between variables, correlational analysis was used. The result of correlation analysis indicates that spirituality and its dimensions (e.g. spiritual virtues, positive outlook on life, spiritual discipline, goodness, spiritual services and moral rectitude), mindfulness and its dimensions (e.g. describing, acting with awareness, non-judgement to inner experiences, non-reactivity to inner experiences), social support and its dimensions (e.g. instrumental support, emotional support, informational support) significantly and positively correlates with psychological wellbeing and its dimensions (e.g. satisfaction, efficiency, sociability, mental health, interpersonal relations). The observed positive correlation suggests that increase in spirituality, mindfulness and social support of elderly people was associated with improved psychological wellbeing of them.